Managerial effectiveness and school performance: case studies of four schools with similar developmental contexts and levels of resources - Arnott, Angela (My University, 2014)
This research has investigated whether the variation in learner results in schools from similar developmental contexts with similar levels of resourcing can be explained by differences in school management of its resources (both physical and human). The research explores the links between effective management and effective schooling.